Improvement in Student Learning Outcomes in Mathematics Using The Numbered Head Together Learning Model Assisted by Snake And Ladder Media in Grade IV of SDN 44/II Karak - Ari Satriadi; Randi Eka Putra; Iri Hamzah (Master of Action Research in Mathematics Classroom, 2026)
Low learning outcomes among fourth-grade students, with only eight students achieving the minimum competency standard (KKTP) with a score of 44.44%, formed the background for this study. This shows that learning achievements in mathematics have not met the minimum competency requirement of 70%. This study aims to describe how the Numbered Heads Together approach, combined with a snakes and ladders game, can improve learning outcomes and processes in the fourth grade of SDN 44/II Karak. Eighteen students were the subjects of this classroom action study. The study was divided into two cycles, each consisting of two meetings led by the researcher. The process included planning, implementation of actions followed by observation, and reflection at the end of each cycle. The results of the study indicate that the process and outcomes of fourth-grade mathematics learning can be improved by applying the Numbered Heads Together paradigm. 1) In meeting I of cycle I, teacher observations showed 68.42% and 80%, but in cycle II, meeting I increased to 84.21% and meeting II to 93.33%. The student observation results were 54.09% in cycle I and 61.28% in meeting II. Meeting I increased to 73.16% in cycle II, while meeting II increased to 63.61%. 2) Student mathematics learning increased from 52.17% in cycle I to 82.60% in cycle II. The Numbered Heads Together paradigm combined with the snake and ladder media can improve the results and process of fourth-grade mathematics learning.